Power, profit and prestige : a history of American imperial expansion - Golub, Philip S. (Pluto Press, 2010)
Power, Profit and Prestige applies incisive historical and sociological analysis to make sense of the United States' post-Cold War imperial behavior. Philip Golub studies imperial identity formation and shows how an embedded culture of force and expansion has shaped American foreign policy. He argues that the US logic of world power and deeply rooted assumptions about American primacy inhibits democratic transformation at domestic and international levels. This resistance to change may lead the US empire into a crisis of its own making. This enlightening book will be particularly useful to students of history and international relations as they explore a world where America is no longer able to set the global agenda.